Ultra-high surface area fibrous silica-zirconia support for renewable energy production by CO2 methanation - Hatta, A. H.; Aishah, Abdul Jalil; Nurul Sahida, Hassan; M. Y.S., Hamid; M. N., Haron; Nabgan, Walid; Bulliard-Sauret, Odin; Mahadi, Bahari; Mohd Asraff, Asmadi; Herma Dina, Setiabudi (Elsevier B.V., 2023)
The spherical mesoporous nickel−loaded fibrous silica zirconia (Ni/FSZr) were successfully synthesized utilizing hydrothermal system followed by impregnation technique and catalytically assessed in CO2 hydrogenation for methane production, a valuable alternative renewable fuel. The Ni/FSZr catalyst, including Ni/SiO2-ZrO2 and Ni/ZrO2, were tested in a fixed-bed reactor at 150 to 500 °C while sustaining atmospheric pressure. Results showed that Ni/FSZr outperformed the other catalysts, with 91.32% CO2 conversion and 91.31% CH4 yield achieved at 500 °C. The catalyst's surface area was found to significantly impact their performance, with Ni/FSZr exhibiting a surface area 28 times higher than the other catalysts. The Ni/FSZr also have moderate basicity and greater amounts of reduced Ni0 which can enhance CO2 methanation activity. Importantly, all catalysts exhibited exceptional stability with no deactivation observed, but the thermal stability of Ni/FSZr was superior, indicating that the fibrous morphology may possibly withstand the formation of coke and resist deactivation. These findings suggest that Ni/FSZr is an effective catalyst for efficient CO2 methanation, which can be beneficial in reducing greenhouse gas emissions and providing a sustainable alternative to traditional fossil fuels.